2006
DOI: 10.1097/01.all.0000200503.77295.bb
|View full text |Cite
|
Sign up to set email alerts
|

The role of Toll-like receptors and related receptors of the innate immune system in asthma

Abstract: The evidence is still being accumulated for the role of Toll-like receptor polymorphisms in the pathogenesis of asthma. There is emerging evidence for the role of CD14 polymorphisms in the development of asthma and atopy. Further studies of innate immunity in asthma and allergy are required, using rigorous study design, measurement of environmental exposure and intermediate phenotypes to demonstrate single nucleotide polymorphism functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 56 publications
1
43
0
1
Order By: Relevance
“…6 Endotoxin or lipopolysaccharide (LPS)-mediated inflammation is believed to be of critical importance in systemic infectious and non-infectious disorders. 7,8 In an animal model, Faas et al 9 demonstrated that infusion of low-dose LPS induces a pre-eclampsia-like syndrome, including hypertension, proteinuria and glomerular endotheliosis. Lipolysaccharide leads to release of pro-inflammatory cytokines through activation of two major pattern recognition receptors present on innate immune cells, including the extracellular Toll-like receptor 2 (TLR2) and TLR4, 10 and the intracellular cryopyrin, a nucleotide-binding oligomerisation domain protein, also known as the caspase-activating recruitment domain.…”
Section: Introductionmentioning
confidence: 99%
“…6 Endotoxin or lipopolysaccharide (LPS)-mediated inflammation is believed to be of critical importance in systemic infectious and non-infectious disorders. 7,8 In an animal model, Faas et al 9 demonstrated that infusion of low-dose LPS induces a pre-eclampsia-like syndrome, including hypertension, proteinuria and glomerular endotheliosis. Lipolysaccharide leads to release of pro-inflammatory cytokines through activation of two major pattern recognition receptors present on innate immune cells, including the extracellular Toll-like receptor 2 (TLR2) and TLR4, 10 and the intracellular cryopyrin, a nucleotide-binding oligomerisation domain protein, also known as the caspase-activating recruitment domain.…”
Section: Introductionmentioning
confidence: 99%
“…This study was performed without a placebo-controlled group. D. pteronyssinus-specific IT induced a significant increase in T oll-like receptors play an important role in bridging innate and adaptive immune responses in the development of pathogen-associated allergic diseases (1,2). Studies showed that TLR2 agonists protect against allergy and asthma by modulating the immune response Th1/Th2 balance (2)(3)(4).…”
mentioning
confidence: 99%
“…Although a strategy to develop vaccines deprived from TLRs has been proposed recently, 23 the activation of TLRs, either directly or through other pattern recognition receptors and signaling machinery, may activate basophils and induce a non IgE-mediated allergic response. 24 A recently published report assessed the role of TLRs in newborns from atopic or asthmatic mothers and showed that TLR2-mediated innate immune responses play a role in increasing the incidence of allergic reactions through the modulation of basophil cytokine secretion and histamine release; furthermore, microbial components released by bacteria, such as formylated peptides, during life, may activate basophils through TLR2 (especially for genetically predisposed infants) to release cytokines associated with an increased incidence of allergic diseases. 25 Activation of non IgE-mediated pathways should elicit CD63 and CD203c upregulation in basophils while skin tests might result negative.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%